A Retrospective Analysis of Colorectal Serrated Lesions from 2005 to 2014 in a Single Center: Importance of the Establishment of Diagnostic Patterns - Priscilla S. P. Oliveira; Rita B. Carvalho; Daniela O. Magro; Michel G. Camargo; Carlos A. R. Martinez; Claudio S. R. Coy (Gastroenterology Research and Practice)
Background. Serrated colorectal lesions are increasingly recognized as an important process in the development of colorectal cancer. Endoscopic and histological diagnosis may be difficult, and knowledge of the serrated lesions is important for the establishment of strategies for treating colorectal lesions. We aimed to analyze serrated lesions diagnosed at a single center and evaluate if there was an increase in their identification over the years. Design and Setting. A retrospective analysis of colonoscopy reports was performed at a specialized center from 2005 to 2014. Methods. Colonoscopy reports about any resected endoscopic lesions were reviewed and subjected to histological diagnosis from 2005 to 2014. Then, serrated lesions were evaluated based on morphological characterization, location, size, occurrence of synchronous lesions, and the patient’s history of colorectal cancer and polyps. Results. A total of 2126 colonoscopy examination reports were reviewed, and 3494 lesions were analyzed. On histopathological examination, 1089 (31.2%) were classified as hyperplastic polyps, 22 (0.6%) as sessile serrated adenomas, and 21 (0.6%) as traditional serrated adenomas. There was an increase in the number of cases of sessile and traditional serrated adenomas diagnosed after 2010. Before 2010, two cases of sessile serrated adenomas and seven cases of traditional serrated adenomas were diagnosed; after 2010, 20 cases of sessile serrated adenoma and 14 cases of traditional serrated adenomas were diagnosed. Conclusion. There was an increase in the diagnosis of sessile serrated adenomas over the years, which can be attributed to better accuracy in colonoscopy and histological classification.